P-027 which is the best method of testicular sperm retrieval for NOA? an answer from 1071 TESE cases in my clinics over 25 years. (30th June 2022) - Kyono, K; Hattori, H; Nakamura, Y; Okuyama, N; Oka, N; Fukuoka, Y; Aono, N; Tai, T; Hashimoto, T
Abstract: Study question: Which improves sperm recovery rate (SRR) for men with non-obstructive azoospermia (NOA), microdissection TESE (m-TESE) or conventional TESE (c-TESE)? Summary answer: SRR of c-TESE vs. m-TESE for NOA was not significant. We need to develop a safer, less-invasive technique with fewer complications and higher SRR. What is known already: m-TESE has been performed for men with NOA since Schlegel P's report (Hum Reprod, 1999). Seminiferous tubules containing many developing germ cells were likely to be larger and more opaque and the ability to find spermatozoa increased from 45% (10/22) to 63% (17/27) after introduction of the microdissection technique. However, Jarvis S et al. (Turek PG group, 2019) reported that at least one site revealed mature sperm in 24 (29.3%) of 82 men with prior failed micro TESE procedures, and sperm were more likely to be found in the testis periphery rather than centrally with FNA mapping. Study design, size, duration: TESE was performed in 1071 azoospermic patients in my clinics; c-TESE was performed for all azoospermic patients between 1996 and 2005 in Sendai; c-TESE for OA and m-TESE for NOA was performed from 2006 in Sendai, and from 2012 in Takanawa. The patients were divided into four groups; 1) FSH≦9.2mIU/ml, Testicular volume(TV)≧15/ml (OA), 2) FSH≦9.2mIU/ml, TV < 15ml, 3) FSH>9.2mIU/ml, TV≧15ml, 4) FSH>9.2mIU/ml, TV < 15ml (NOA). Participants/materials, setting, methods: c-TESE was performed in 178 azoospermic men (50, 12, 7, 109, respectively) in 1996-2005. c-TESE was performed in 181 patients (131, 26, 15, 9, respectively) and m-TESE was performed in 541 patients (56, 33, 35, 416, respectively) in 2006 -2020. SRR, pregnancy rate (PR), and birth rate (BR) in 1996-2005 were compared with those in 2006-2020. Main results and the role of chance: Statistical analysis was performed by chi-square analysis. SRR in c-TESE was 96.0% (48/50) in group 1 (OA) vs. 36.7% (40/109) in group 4 (NOA) in Sendai between 1996 and 2005 (P < 0.001). SRR of c-TESE was 36.7% (40/109) in group 4 (NOA, in Sendai, 1996-2006), whereas SRR of m-TESE was 31.3% (130/416) in group 4 (NOA, in Sendai and Takanawa, 2006-2020). There was no significant difference (np). Total SRR of conventional TESE for all azoospermic patients between 1996 and 2005 was 54.9% (96/175), whereas total SRR of c-TESE for OA and m-TESE for NOA between 2006 and 2020 was 51.7% (373/721). NOA rate 4) of azoospermic patients of 1996-2005 and that of 2006-2020 was 61.2% (109/178) and 58.9% (425/721), respectively. There was no significant difference (np). PR was 37.4% (61/163) and BR was 31.9% (52/263) in c-TESE (1996-2005), PR was 39.6% (388/980), and BR was 27.6% (270//980) in both c-TESE and m-TESE (2006–2020). There was a significant difference in birth rate (P < 0.05). In conclusion, SRR, PR, and BR were not improved even after m-TESE was performed. Considering the fact that m-TESE cannot find sperm thoroughly, adopting other techniques such as sperm fine-needle aspiration may be required. Limitations, reasons for caution: Not applicable. Wider implications of the findings: We could not show the effectiveness of m-TESE compared with c-TESE. However, the total volume of seminiferous tubules collected by c-TESE was the higher. The new one-step fine-needle aspiration has the potential to achieve higher sperm yield with fewer complications. Further advanced technology will hopefully improve the SRR in NOA. Trial registration number: none